(11)C-CUMI-101, a PET Radioligand, Behaves as a Serotonin 1A Receptor Antagonist and Also Binds to α(1) Adrenoceptors in Brain - Shrestha, Stal Saurav (J Nucl Med, 2014)
The PET radioligand (11)C-CUMI-101 was previously suggested as a putative agonist radioligand for the serotonin 1A (5-hydroxytryptamine 1A [5-HT(1A)]) receptor in recombinant cells expressing human 5-HT(1A) receptor. However, a recent study showed that CUMI-101 behaved as a potent 5-HT(1A) receptor antagonist in rat brain. CUMI-101 also has moderate affinity (Ki = 6.75 nM) for α(1) adrenoceptors measured in vitro. The current study examined the functional properties and selectivity of CUMI-101, both in vitro and in vivo. METHODS: The functional assay was performed using (35)S-GTPγS (GTP is guanosine triphosphate) in primate brains. The cross-reactivity of CUMI-101 with α(1) adrenoceptors was performed using in vitro radioligand binding studies in rat, monkey, and human brains as well as in vivo PET imaging in mouse, rat, and monkey brains. RESULTS: CUMI-101 did not stimulate (35)S-GTPγS binding in primate brain, in contrast to 8-OH-DPAT, a potent 5-HT(1A) receptor agonist. Instead, CUMI-101 behaved as a potent 5-HT(1A) receptor antagonist by dose-dependently inhibiting 8-OH-DPAT–stimulated (35)S-GTPγS binding. Both in vitro and in vivo studies showed that CUMI-101 had significant α(1) adrenoceptor cross-reactivity. On average, across all 3 species examined, cross-reactivity was highest in the thalamus (>45%) and lowest in the neocortex and cerebellum (<10%). PET imaging further confirmed that only preblocking with WAY-100635 plus prazosin decreased (11)C-CUMI-101 brain uptake to that of self-block. CONCLUSION: CUMI-101 behaves as a 5-HT(1A) receptor antagonist in primate brain, with significant, regional-dependent α(1) adrenoceptor cross-reactivity, limiting its potential use as a PET radioligand in humans.